China's macroeconomic policy trifecta and challenges to the governance of the global trading system - Mark Kruger (Centre for International Governance Innovation (CIGI), 2020)
A ceasefire has been called in the trade war between the United States and China, but there is lingering uncertainty that will stifle aggregate spending until a "peace treaty" is signed. China is thus currently undertaking a precarious policy trifecta balancing act - trying to maintain steady GDP growth while promoting financial stability and managing protectionist pressures. Attaining any one of these objectives makes achieving any of the others a daunting task. Putting the trade war into simple terms, the United States is worried about the size of its bilateral trade deficit with China and is concerned that China's industrial policies give it an unfair advantage in international trade. The United States does not believe the World Trade Organization (WTO), which is tasked with setting the rules for how international trade should be conducted, can effectively constrain China's behaviour. And the United States' distrust of the WTO goes beyond its concerns with China. As the world's largest trader, China has the most to lose from a breakdown of the WTO. This paper offers recommendations on the policies that China might pursue to achieve its macroeconomic goals and step up to take a leadership role in WTO reform.
Keywords: 330; Trade Conflict; Economic Policy; Trade Balance; China; USA; Handelskonflikt; Wirtschaftspolitik; Chinesisch; Handelsbilanz; Amerikanisch; China; USA